2015
DOI: 10.1038/ejhg.2015.168
|View full text |Cite
|
Sign up to set email alerts
|

Children with sex chromosome trisomies: parental disclosure of genetic status

Abstract: Sex chromosome trisomies (SCTs) are frequently diagnosed, both prenatally and postnatally, but the highly variable childhood outcomes can leave parents at a loss on whether, when and how to disclose genetic status. In two complementary studies, we detail current parental practices, with a view to informing parents and their clinicians. Study 1 surveyed detailed qualitative data from focus groups of parents and affected young people with either Trisomy X or XYY (N = 34 families). These data suggested that decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…The child's participation is also an issue. As we noted in our discussion, we previously found that parents are more likely to tell their child about the trisomy if the child is experiencing difficulties (Gratton et al, 2016), in which case the child can feel a sense of relief at having an explanation for why they are different from others. On the other hand, there is likely to be an opposing potential bias, which is that children who are anxious about social or communicative difficulties are less likely to assent to take part, even if parents want them to.…”
Section: Sampling Biassupporting
confidence: 51%
See 1 more Smart Citation
“…The child's participation is also an issue. As we noted in our discussion, we previously found that parents are more likely to tell their child about the trisomy if the child is experiencing difficulties (Gratton et al, 2016), in which case the child can feel a sense of relief at having an explanation for why they are different from others. On the other hand, there is likely to be an opposing potential bias, which is that children who are anxious about social or communicative difficulties are less likely to assent to take part, even if parents want them to.…”
Section: Sampling Biassupporting
confidence: 51%
“…the General Communication Composite of the CCC-2. Furthermore, for ethical reasons, we were only able to study children who knew about their sex chromosome trisomy: we know from our previous study that these tend to be children with more severe problems, where the trisomy may be disclosed in order to help the child understand about their difficulties (Gratton et al, 2016). It is therefore likely that even our Low Bias group may overestimate the extent of language difficulties in childhood, because those without any difficulties would be less likely to take part.…”
Section: Discussionmentioning
confidence: 99%
“…However, another bias that is impossible to control is determined by who volunteers to take part in the research. In this study, children could be included only if they knew about their chromosome status; our prior research has shown that parents are more likely to disclose this information when the child is experiencing difficulties ( Gratton et al , 2016). Children were also required to assent to take part in the study, after viewing a video that provided information about what was involved.…”
Section: Discussionmentioning
confidence: 99%
“…the General Communication Composite of the Children’s Communication Checklist-2. Furthermore, for ethical reasons, we were only able to study children who knew about their sex chromosome trisomy: we know from our previous study that these tend to be children with more severe problems, where the trisomy may be disclosed in order to help the child understand about their difficulties ( Gratton et al ., 2016). It is therefore likely that even our Low Bias group may overestimate the extent of language difficulties in childhood, because those without any difficulties would be less like to take part.…”
Section: Discussionmentioning
confidence: 99%